2007
DOI: 10.1038/nature06015
|View full text |Cite
|
Sign up to set email alerts
|

Northern Hemisphere forcing of climatic cycles in Antarctica over the past 360,000 years

Abstract: The Milankovitch theory of climate change proposes that glacial-interglacial cycles are driven by changes in summer insolation at high northern latitudes. The timing of climate change in the Southern Hemisphere at glacial-interglacial transitions (which are known as terminations) relative to variations in summer insolation in the Northern Hemisphere is an important test of this hypothesis. So far, it has only been possible to apply this test to the most recent termination, because the dating uncertainty associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
457
2
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 499 publications
(499 citation statements)
references
References 33 publications
32
457
2
8
Order By: Relevance
“…Moreover, numerous studies show strong palaeoenvironmental and palaeoclimatic changes at time of the increasing Northern Hemisphere insolation during the mid-MIS 6 (e.g. Petit et al, 1999;Ayalon et al, 2002;Kawamura et al, 2007;Hodge et al, 2008;Wang et al, 2008), corroborating the concept of a reorganisation of the southern margin of the European ice sheet and Alpine glaciers within the ca. 160-150 ka interval.…”
Section: Marine Isotope Stage 6 Andmentioning
confidence: 68%
See 1 more Smart Citation
“…Moreover, numerous studies show strong palaeoenvironmental and palaeoclimatic changes at time of the increasing Northern Hemisphere insolation during the mid-MIS 6 (e.g. Petit et al, 1999;Ayalon et al, 2002;Kawamura et al, 2007;Hodge et al, 2008;Wang et al, 2008), corroborating the concept of a reorganisation of the southern margin of the European ice sheet and Alpine glaciers within the ca. 160-150 ka interval.…”
Section: Marine Isotope Stage 6 Andmentioning
confidence: 68%
“…280-260 ka and ca. 160-150 ka intervals (Kawamura et al, 2007) while glaciomarine conditions overran site ODP-980 and the Bay of Biscay despite the significant rise of the Northern Hemisphere summer insolation. Even if the discharges were not always as important as at ca.…”
Section: Comments On the Timing Of Major 'Fleuve Manche' Discharges Amentioning
confidence: 99%
“…Recently, it has been shown that the entrapped air in the ice is also related to local orbital insolation variations (Bender, 2002;Raynaud et al, 2007). The orbital signal in the ice would permit dating ice core records independently from other methods (Kawamura, 2009;Kawamura et al, 2007) if the complete chain of processes involved in the signal formation at the surface, in the firn column and at the firn-ice transition was understood. Presently, it is believed that local insolation affects the microstructure of the firn at the surface, which is unaltered during the densification and recrystallization process in the firn.…”
Section: Introductionmentioning
confidence: 99%
“…Records of Loess [91] and marine [92] sediments also show a similar glacial-interglacial cycle, suggesting a synchronization of global climate change on orbital timescale, reflecting the periodic variations of the earth's orbital parameters. According to Milankovitch theory, the main driving factor for the glacial-interglacial cycle of climate is the amount of summer solar radiation received by the Earth at high northern latitude [93]. The signal of the summer solar radiation is conveyed through variations of greenhouse gas concentration and thermohaline circulation intensity.…”
Section: Temperature Change At Orbital Timescalementioning
confidence: 99%